PENGEMBANGAN E-MODUL BERBANTUAN HEYZINE FLIPBOOK BERBABSIS RME UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN GROWTH MINDSET - Hikmi Inayah; Supratman; Diar Veni Rahayu (Jurnal Ilmiah Matematika Realistik, 2026)
The purpose of this study is to develop an e-module using Heyzine Flipbook on single-variable linear equations based on Realistic Mathematics Education (RME) to improve the critical thinking skills and growth mindset of seventh-grade students at Dharma Ksatria Junior High School in Pangandaran. The background of the problem includes low thinking skills due to a lack of interactive digital media and the prevalence of a fixed mindset among students, which hinders the understanding of mathematical concepts from real-world contexts. Previous studies focused solely on critical thinking skills. This research is an R&D (Research and Development) study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 2 subject matter experts, 2 media experts, 1 mathematics teacher, 5 students in a small pilot test, and 20 students in the experimental class. Data collection techniques included observation, structured interviews, validation questionnaires, critical thinking tests (pretest-posttest), user response questionnaires, and growth mindset questionnaires. Data analysis utilized the feasibility percentage (>81% highly feasible), N-Gain (>0.7 high), effect size (>1.00 strong), Shapiro-Wilk normality test, and Wilcoxon test (Sig. < 0.05). The results of the study showed that the subject matter expert validation achieved a score of 100%, and the subject matter experts scored 85% in the “highly valid” category, while the growth mindset questionnaire met the “very good” criteria. The results of the hypothesis testing led to the conclusion that “there was a significant improvement in students’ critical thinking skills after using the RME-based e-module on single-variable linear equations supported by the Heyzine flipbook.” The students’ growth mindset outcomes after using the RME-based single-variable linear equation e-module supported by the Heyzine flipbook, across each aspect of the growth mindset, were as follows: regarding belief in challenges, it fell into the “High” category; regarding belief in ability, effort, criticism, and the success of others, it fell into the “Very high” category.